2020
DOI: 10.1002/1348-9585.12180
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of night shift and menstrual cycle characteristics in Japanese nurses working under two or three rotating shifts

Abstract: The menstrual cycles is controlled by the cyclical secretion of reproductive hormones, including luteinizing hormone, follicle-stimulating hormone, estrogen, and progesterone, which are regulated by the hypothalamus-pituitary-ovarian axis. 1 The absence of menses ≥3 months is diagnosed as secondary amenorrhea. Over 50% of secondary amenorrhea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Nevertheless, the debate continues regarding the association between menstrual problems and working shift patterns. A study of 1,249 nurses in 2020 reported that working in two or three rotating shifts increased the incidence of irregular menstrual cycles compared to no night shifts; however, the incidence of dysmenorrhea affecting their work was not significantly different according to shift patterns (p = 0.429) [ 15 ]. A recent prospective epidemiological study of 188 Spanish nurses revealed that rotating shift work patterns did not increase the risk of menstrual disorders, including prolonged duration, dysmenorrhea, prolonged duration of dysmenorrhea, and excessive bleeding [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the debate continues regarding the association between menstrual problems and working shift patterns. A study of 1,249 nurses in 2020 reported that working in two or three rotating shifts increased the incidence of irregular menstrual cycles compared to no night shifts; however, the incidence of dysmenorrhea affecting their work was not significantly different according to shift patterns (p = 0.429) [ 15 ]. A recent prospective epidemiological study of 188 Spanish nurses revealed that rotating shift work patterns did not increase the risk of menstrual disorders, including prolonged duration, dysmenorrhea, prolonged duration of dysmenorrhea, and excessive bleeding [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been still controversy so far regarding the association between shift work and gynecologic symptoms, including menstrual disorders [13][14][15]. Moreover, there is no domestic research on the correlation between pattern of work and gynecologic healthcare behavior in nursing staffs in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study found no significant association between average hours of sleep, shift work, and MCL [ 4 ], others indicate that MCL is impacted by disrupted circadian rhythm [ 5 , 39 , 40 ▪ ]. The frequency of night shifts is associated with shortened MCL and shift work schedules are associated with increased likelihood of cycle irregularity in a study containing both cross-sectional and nested case–control components [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Particularly concerning is that these changes had not recovered 2 years later [ 39 ]. Another cross-sectional study similarly found that rotating shifts were associated with MCL irregularity [ 40 ▪ ]. Sleeping for fewer than 6 h per night is also significantly associated with short MCL (OR = 3.7; 95% CI 1.1–12.7) and nonsignificantly associated with long MCL (OR = 1.7, 95% CI 0.8–3.7) in a prospective cross-sectional study, leading the authors to suggest a causal association between insufficient sleep and metabolic abnormalities [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…Проте дослідження психофункціонального стану у пацієнток з АМК є поодинокі. Вони стосуються, переважно, вивчення розладів МЦ у жінок, які працюють в напружених умовах [5].…”
unclassified